Visitor motivations and use of Information communication technology at a coastal destination: the case of limbe – Cameroon - Paul Nkemngu Acha-Anyi; Vikelwa Judith Nomnga (Cogent Social Sciences, 2024)
Understanding visitor motivations provides an opportunity for destination managers to be better prepared to meet visitor expectations. In the increasingly competitive tourism environment, the uptake of ICT, particularly in developing countries avails an additional avenue to enhance visitors’ experiences and simultaneously promote the destination. This study aims to explore tourists’ motivations for visiting the coastal town of Limbe and the use of Information Communication Technology to enhance the experience. A questionnaire was used to collect data from 250 randomly selected visitors to the beachfront. Using both exploratory statistics and analysis of variance, the study finds that the motivation to rest and rejuvenate is rated quite highly (mean score = 3.49) by the respondents and ICT is used mainly to capture and share experiences (3.47). Further examination of the analysis of variance reveals no statistically significant difference between females and males (p = 0.2), but statistically significant differences among age groups (p = 0.05). This study recommends, inter alia, that destinations such as Limbe make ICT a functional and complementary aspect of their product experience. The study contributes important insights to the literature on visitor motivations and the use of ICT in the global South and Cameroon in particular.